Discovery of Viridotheres Manning, 1996 in the southwestern Pacific and first record of Discorsotheres camposi Ahyong, 2018 from New Caledonia (Crustacea: Brachyura: Pinnotheridae) - Ahyong, Shane T. (Zootaxa, 2020)
The pinnotherid crab genus, Viridotheres Manning, 1996, is recorded for the first time from the southwestern Pacific in the new species, V. asaphis, described based on specimens from Australia and New Caledonia. The new species most closely resembles V. sanguinolariae (Pillai, 1951) from India, differing chiefly in the proportional length of the walking legs; both species are hosted by bivalve molluscs of the family Psammobiidae, but of different genera. The pinnotherid crab Discorsotheres camposi Ahyong, 2018, an associate of the bivalve Spondylus, is recorded for the first time from New Caledonia. Fifteen species of pinnotherid are now known from Australian waters and five from New Caledonia.